2022
DOI: 10.3390/su142315591
|View full text |Cite
|
Sign up to set email alerts
|

Tilt Angle and Orientation Assessment of Photovoltaic Thermal (PVT) System for Sub-Saharan Tropical Regions: Case Study Douala, Cameroon

Abstract: Photovoltaic systems when integrated into a building structure can satisfy the world’s energy requirements at a competitive cost by providing onsite electrical and thermal energies for domestic appliances. The energy yield of the photovoltaic system is affected by the intensity of the solar radiation, wind speed, tilt angle, orientation, geographical location, etc. This paper presents an optimisation model of the tilt angle and orientation of a photovoltaic thermal system. A methodology has been developed to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In today's dynamic world of socio-economic and environmental challenges, energy conversion, conservation and utilization systems are the subject of much controversy in scientific and related fields [ [1] , [2] , [3] , [4] , [5] , [6] ]. The PTSC, known as one of the world's leading energy conversion systems, offers multitudes of possibilities for the efficient conversion, management, production and use of solar energy [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In today's dynamic world of socio-economic and environmental challenges, energy conversion, conservation and utilization systems are the subject of much controversy in scientific and related fields [ [1] , [2] , [3] , [4] , [5] , [6] ]. The PTSC, known as one of the world's leading energy conversion systems, offers multitudes of possibilities for the efficient conversion, management, production and use of solar energy [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…This must be weighed against the additional costs associated with increasing the tilt angle of a solar PV module, such as additional costs for supporting structures, higher labour [11] and installation costs [12], and an increased risk of damage due to strong winds or snow loads [13]. Therefore, while it is important to consider the tilt angle and orientation of a solar PV module when selecting one for installation, this must be done in a balanced way to ensure that the costs are kept to a minimum [12] and that the efficiency of the module is maximized [11] while also ensuring that the risks of damage are minimized [14].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous researchers have studied the effect of soiling and the optimum tilt angle on PV performance and found that soiling can reduce photovoltaic efficiency by up to 50% [11], while the optimum tilt angle can increase efficiency by up to 20% [12]. As such, maintaining clean solar panels and optimizing their tilt angle can have a significant positive impact on photovoltaic efficiency and should be taken into account when installing a solar PV system for maximum energy production.…”
Section: Introductionmentioning
confidence: 99%